INVENTARISASI FLORA DARAT DI DESA MUARA AMPOLU KECAMATAN MUARA BATANGTORU - Dwi Ratna Anjaning Kusuma Marpaung (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2024)
Muara Ampolu Village located in Batangtoru District, Deli Serdang Regency is a terrestrial ecosystem with hill topography which is generally used as a production forest for oil palm cultivation and generally has natural forest vegetation. The increasing opening of oil palm commodity production is in line with land clearing in the study area and is expected to affect the condition of the surrounding environmental components, especially terrestrial flora. Inventory was conducted to determine the diversity of terrestrial flora species found in the study area and to minimize the rate of loss of terrestrial flora species diversity in the area. Terrestrial flora found in the study area includes 41 species belonging to 31 families in residential and agricultural areas; while in the hill forest area, 285 species belonging to 43 families were obtained. Terrestrial flora in settlements are plants deliberately planted and/or left by residents because they have benefits as food, aesthetics, shade, herbal medicine, and as ground cover and other functions, while terrestrial flora in hill forests is dominated by pioneer plants such as Mallotus spp. and Macaranga spp. and the presence of Ficus padana species; climax forest vegetation such as Castanopsis spp., and from the Dipterocarpaceae family namely Dryobalanops spp., Shorea spp., Dipterocarpus spp.; and invasive species such as ilalang (Imperata cylindrica) and sandukan (Melastoma malabatricum).